Genetic and molecular control of the flowering time in soybean (Glycine max (L.) Merrill) - Islam, Md Rasadul (Research in Agriculture Livestock and Fisheries, 2022)
Photoperiod response to flowering is one of the most vital factors that affect in regional adaptation and yield in soybean. Soybean adaption at high latitude areas (long-day) requires early flowering and low photoperiod sensitive cultivars; adaptation to low latitudes (short-day) areas needs delayed flowering cultivars, which maximize vegetative growth and seed yield. This paper represents a genetic and molecular regulation of flowering time in soybean, which will help broad adaptability across latitudes. It is revealed that one to eleven main genes control the flowering time in soybean. The FT family of flowering integrators plays a central role in controlling the flowering time. The juvenile growth phase (JGP) determines the development rate for flowering; a long JGP results in the lengthening of the vegetative period and increases the soybean production in low latitude areas. This review outlines the JGP-related gene in soybean. We emphasize the interaction between major genes and QTLs for flowering in soybean. Several major genes and quantitative trait loci (QTLs) for flowering interact with one another including the environment to greatly influence flowering time. The molecular ground information of the flowering in Arabidopsis will help to understand the molecular dissection of flowering in soybean. This information could be used for breeding of high‐yielding soybean cultivars in different latitudinal areas. Res. Agric., Livest. Fish.9(1): 1-10, April 2022